Conventional DC Voltage Operating System for High Speeed Traction Power Supplies Using LLC-HPQC Control - Ch. Lenin Babu; P. Harinath Reddy; T. Reddi Sekhar (Institute of Advanced Engineering and Science, 2015)
In this paper a hybrid power quality compensator (HPQC) is proposed for compensation in cophase traction power supply and minimum dc operation voltage is achievable for high-speed traction power supply. The parameter design procedure for minimum dc operation voltage in HPQC as well as minimum voltage rating with load PF is discussed. The detailed discussions of proposed circuit configurations of HPQC are provided in section II, together with comparison with conventional RPC. In comparison with conventional railway power compensator proposed HPQC can achieve reduced dc link voltage level. It is also verified through simulations results that the LLC-HPQC would operate at the minimum voltage with the proposed parameter design. HPQC is able to provide system unbalances, reactive power, and harmonic compensation in cophase traction power with reduced operation voltage. The cophase traction power supply with proposed HPQC is suitable for high-speed traction applications.